Maternal smoking habits are associated with differences in infants' long-chain polyunsaturated fatty acids in whole blood: a case-control study. Issue 5 (21st April 2008) - Agostoni, C; Riva, E; Giovannini, M; Pinto, F; Colombo, C; Risé, P; Galli, C; Marangoni, F
Abstract : Objective: To study the effects of maternal smoking on the status of long-chain polyunsaturated fatty acids (LCPUFA) in infants' whole-blood lipids. Design: A case-control matched study planned on the basis of preliminary observations. Setting: Maternity ward. Patients: A total of 159 healthy, term, breastfed infants with weight appropriate for gestational age, subdivided (53 per group) into those born to non-smokers (reference), smokers (⩾5 cigarettes per day) who either stopped within the first trimester of pregnancy (early smokers) or who continued througout pregnancy (late smokers). Interventions: The fatty acid profile of 4-day-old infants was determined on whole blood. Results: Higher levels of linoleic (LA) and alpha-linolenic acid (ALA) and lower levels of the metabolic products di-homo-gammalinolenic (DHGLA) and arachidonic (AA), of the n-6 series, and docosahexaenoic acid (DHA), of the n-3 series, were found in infants born to late smokers compared with the reference group. The DHGLA/LA and AA/DHGLA ratios in the n-6 series and DHA/ALA in the n-3 series, which are indices of the metabolic processes in LCPUFA synthesis, were lower in infants born to smokers compared with those born to non-smokers. Infants born to early smokers showed n-6 PUFA levels and ratios similar to references and n-3 parameters closer to those born to late smokers. No dietary differences were found among the three groups of mothers. All the independent associations with smoking persisted after adjustment for maternal covariates. Pre-pregnancy body weight, which is lower in late smokers compared with non-smokers, independently correlated with LCPUFA levels in both series. Conclusions: Maternal smoking is associated with a reduction in LCPUFA pools in infants, which might have structural and functional consequences.